Formulasi dan Evaluasi Sediaan Roll on Aromaterapi Minyak Atsiri Buah Andaliman (Zanthoxylum Acanthopodium Dc.) - Novelia Zwi Dwinayanti Silaban; Roy Indrianto Bangar; Asyrun Alkhairi Lubis (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Andaliman (Zanthoxylum acanthopodium DC.) is an endemic spice from North Sumatra with significant therapeutic potential derived from its essential oils. Terpenoid compounds such as geranyl acetate, limonene, and citronellol in andaliman are recognized for their efficacy in aromatherapy to alleviate nausea and vomiting. This study aims to construct an aromatherapy roll-on formulation using andaliman fruit essential oil and to evaluate its physical characteristics and safety profile. The research employed a laboratory experimental method, utilizing the Stahl steam distillation technique for essential oil isolation. The preparations were formulated into three concentration variations: F0 (0%), F1 (5%), and F2 (10%). Evaluation parameters included organoleptic properties, homogeneity, viscosity, pH value, dermal irritation tests, and hedonic (preference) tests. The results demonstrated that all formulas maintained excellent physical stability and homogeneity. The pH values ranged from 5.52 to 6.06, which is considered safe as it aligns with the physiological pH of human skin (4.5–6.5). Irritation tests confirmed that the formulations did not trigger adverse skin reactions in respondents. According to the hedonic test, panelists showed high preference for aroma, texture, and comfort, although the scent longevity requires further optimization due to the volatile nature of the essential oil. Overall, the andaliman essential oil aromatherapy roll-on meets the physical quality and safety standards for topical preparations.